"Assurance that the world holds far more good than bad":The Pedagogy of Memory at the Oklahoma City National Memorial Museum. Issue 1 (2nd January 2019) - Obermark, Lauren
Abstract : The Oklahoma City National Memorial Museum (OKCNMM) must balance respectful remembrance with broad education about the 1995 terrorist attack that killed one hundred and sixty-eight people. Epideictic and material rhetorics prevail throughout the OKCNMM, communicating uplifting messages about the effects of the bombing while also prompting visitors to create their own complex, productively uncomfortable pathways toward understanding. In this process, civic engagement through rhetorical processes is encouraged; the museum models and creates space to practice reflective dwelling, critical thinking, discussion, and composition, offering a rhetorical education that can circulate far beyond this single site.